AN ANALYSIS OF ASSESSMENT USED IN THE ENGLISH TEXTBOOK OF MERDEKA BELAJAR CURRICULUM FOR THE FIRST-YEAR STUDENTS OF JUNIOR HIGH SCHOOL - Nurul Maulida; Sukri Adani (Yayasan Nusantara Hasana Berdikari, 2023)
Assessment is one of the important processes in education that is useful for assessing the effectiveness of learning and curriculum achievement. The assessment process is very important to evaluate as well as improve the learning process. The aimed this study is to explore the dominant forms of assessments used in English in Mind the textbook of Merdeka Belajar curriculum for first-year students of Junior High School and to know the types of assessment used in the English textbook of Merdeka Belajar curriculum for first-year students of Junior High School. The writer used the mixed method. Based on the data analysis the writer found 22 types of assessments of English in Mind in which it devided into 16 assessments after analyzed by each aspect skills, they are directed responses, read-aloud, sentence/dialogues complexion andoral questionnaire, pictures-cued task, translation, questionand answer, giving instruction and direction, information transfer, dictation, listening cloze, sentence repetition, reading aloud, written response, multiple choice, matching task, short answer, grammatical transformation, and vocabulary assessment. Then, the dominant assessment used in the English textbook of Merdeka Belajar curriculum for the first-year students of Junior High School was a grammatical transformation from writing skills.